Public Choice III - Mueller, Dennis C (Cambridge University Press, 2003)
This book represents a considerable revision and expansion of Public Choice II (1989). As in the previous editions, all of the major topics of public choice are covered. These include: why the state exists, voting rules, federalism, the theory of clubs, two-party and multiparty electoral systems, rent seeking, bureaucracy, interest groups, dictatorship, the size of government, voter participation, and political business cycles. Normative issues in public choice are also examined. The book is suitable for upper level courses in economics dealing with politics, and political science courses emphasizing rational actor models.